2015
DOI: 10.1371/journal.pone.0120413
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Results in Tissue-Specific Changes in Bioenergetics and Redox State

Abstract: Intermittent fasting (IF) is a dietary intervention often used as an alternative to caloric restriction (CR) and characterized by 24 hour cycles alternating ad libitum feeding and fasting. Although the consequences of CR are well studied, the effects of IF on redox status are not. Here, we address the effects of IF on redox state markers in different tissues in order to uncover how changes in feeding frequency alter redox balance in rats. IF rats displayed lower body mass due to decreased energy conversion eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 39 publications
3
55
2
1
Order By: Relevance
“…The increase in state 3 mitochondrial respiration combined with a decrease in state 4 respiration suggests a selective upregulation of the capacity to produce ATP without a concomitant increase in energy expended via proton leak (Kadenbach, ). The state‐specific responses of the mitochondria that we observed during fasting contrast with many studies that show comparable directional changes in state 3 and state 4 respiratory capacities (Brown & Staples, , ; Chausse et al., ). Those studies were in mammals that experience much briefer periods of food limitation in comparison with the fish in this study, which may help explain the differences observed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The increase in state 3 mitochondrial respiration combined with a decrease in state 4 respiration suggests a selective upregulation of the capacity to produce ATP without a concomitant increase in energy expended via proton leak (Kadenbach, ). The state‐specific responses of the mitochondria that we observed during fasting contrast with many studies that show comparable directional changes in state 3 and state 4 respiratory capacities (Brown & Staples, , ; Chausse et al., ). Those studies were in mammals that experience much briefer periods of food limitation in comparison with the fish in this study, which may help explain the differences observed.…”
Section: Discussioncontrasting
confidence: 99%
“…To meet that challenge, animals utilize physiological responses that reduce their metabolic requirements and thus enhance their chance of survival (Secor & Carey, ). A central component of such responses is the alteration of mitochondrial energy metabolism (Bermejo‐Nogales, Calduch‐Giner, & Pérez‐Sánchez, ; Chausse, Vieira‐Lara, Sanchez, Medeiros, & Kowaltowski, ; Monternier, Marmillot, Rouanet, & Roussel, ). However, mitochondria are also a major source of reactive oxygen species (ROS) that have the potential to cause oxidative damage (Brand, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4b). The discrepancy with previous data could be due to the variation of expression patterns of HDAC isoforms among tissues (Chausse, Vieira‐Lara, Sanchez, Medeiros, & Kowaltowski, 2015). …”
Section: Resultscontrasting
confidence: 88%
“…Because mitochondria are cornerstone organelles implicated in metabolic responses to fasting (Monternier et al, 2014), but also the first site of production of damaging reactive oxygen species (ROS) (Andreyev et al, 2005), direct oxidative costs to prolonged fasting may be expected (e.g. Chausse et al, 2015;Geiger et al, 2012;Sorensen et al, 2006;Wasselin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%